Practical Experience with Woody Biomass in a Down-Draft Gasifier - Wolff, Deidre; Walsh, Eilin; McDonnell, Kevin P. (Journal of Technology Innovations in Renewable Energy, 2013)
Gasification is the cleanest method of obtaining energy from fossil fuels, but with increasing awareness of depleting fossil fuel reserves attention has shifted towards renewable sources of energy. Any carbonaceous material can be gasified to generate high-value end-products from otherwise potentially low-value materials. Gasification can also generate energy from purpose-grown bioenergy crops, and Ireland has an ideal climate to produce woody biomass for energy generation. This update outlines some preliminary results from an investigation into the most suitable woody feedstock for small-scale localised gasification to produce a synthetic gas suitable for use in internal combustion engines. Argentinean- and German-standard wood pellets and Irish-grown willow chips were gasified in a down-draft gasifier. Operation of the gasifier led to the observation that the willow chips bridged within the feedstock hopper which prevented completion of gasification. Implementing a stirring bar in the feedstock hopper prevented bridging and gasification was then successful. Collection of the gas produced during gasification of willow chip was unsuccessful, however gas composition analysis indicates pellets which meet the German-standard are more suitable than Argentinean-standard pellets for use in a down-draft gasifier; work is underway to determine the composition of willow-derived synthetic gas to determine the most suitable feedstock for decentralised gasification by rural communities in Ireland as part of smart farming systems.